Proofs to one inequality conjecture for the non-integer part of a nonlinear differential form - Mei Chen (Journal of Inequalities and Applications, 2017)
Abstract We prove the conjecture for the non-integer part of a nonlinear differential form representing primes presented in (Lai in J. Inequal. Appl. 2015:Article ID 357, 2015) by using Tumura-Clunie type inequalities. Compared with the original proof, the new one is simpler and more easily understood. Similar problems can be treated with the same procedure.